Indirect costs of rheumatoid arthritis - Raciborski, Filip (Reumatologia, 2015)
It is estimated that in Poland about 400,000 persons in general suffer from inflammatory joint diseases, including rheumatoid arthritis (RA). Epidemiological surveys documenting the frequency and disturbance of musculoskeletal disorders in the Polish population are few in number. Most of the estimations are based on epidemiological data from other countries (prevalence of 0.5–1%). According to the data of the National Health Fund in Poland 135,000–157,000 persons in total are treated because of rheumatoid arthritis per year [ICD10 (International Statistical Classification of Diseases and Related Health Problems): M05, M06]. In the case of this group of diseases indirect costs significantly outweigh the direct costs. Indirect costs increase together with activity level of the disease. The cost analysis of productivity loss of RA patients indicates that sickness absenteeism and informal care are the most burdensome. At the national level it amounts in total from 1.2 billion to 2.8 billion PLN per year, depending on the method of analysis. These costs could be significantly reduced through early diagnosis and introduction of effective treatment.